Shift of microbial diversity and function in high-efficiency performance biotrickling filter for gaseous xylene treatment. (2nd September 2019) - Li, Mingxue; Shi, Yantao; Li, Yixuan; Sun, Yizhe; Song, Chunhui; Huang, Zhiyong; Yang, Zongzheng; Han, Yifan
ABSTRACT: Xylene is the main component of many volatile industrial pollution sources, and the use of biotechnology to remove volatile organic compounds (VOCs) has become a growing trend. In this study, a biotrickling filter for gaseous xylene treatment was developed using activated sludge as raw material to study the biodegradation process of xylene. Reaction conditions were optimized, and long-term operation was performed. The optimal pH was 7.0, gas-liquid ratio was 15:1 ( v / v ), and temperature was 25 °C. High-throughput sequencing technique was carried out to analyze microbial communities in the top, middle, and bottom layers of the reactor. Characteristics of microbial diversity were elucidated, and microbial functions were predicted. The result showed that the removal efficiency (RE) was stable at 86%–91%, the maximum elimination capacity (EC) was 303.61 g·m −3 ·hr −1, residence time was 33.75 sec, and the initial inlet xylene concentration was 3000 mg·m −3, which was the highest known degradation concentration reported. Kinetic analysis of the xylene degradation indicated that it was a very high-efficiency-activity bioprocess. The r max was 1059.8 g·m −3 ·hr −1, and K s value was 4.78 g·m −3 in stationary phase. In addition, microbial community structures in the bottom and top layers were significantly different: Pseudomonas was the dominant genus in the bottom layer, whereas Sphingobium was dominant in the top layer. The results showed that intermediate metabolites of xylene could affect the distribution of community structure. Pseudomonas sp. can adapt to high concentration xylene–contaminated environments. Implications: We combined domesticated active sludge and reinforced microbial agent on biotrickling filter. This system performed continuously under a reduced residence time at 33.75 sec and high elimination capacity at 303.61 g·m −3 ·hr −1 in the biotrickling reactor for about 260 days. In this case, predomestication combined with reinforcing of microorganisms was very important to obtaining high-efficiency results. Analysis of microbial diversity and functional prediction indicated a gradient distribution along with the concentration of xylene. This implied a rational design of microbial reagent and optimizing the inoculation of different sites of reactor could reduce the preparation period of the technology.